Methane Adsorption Microcalorimetry of Activated Carbon Fibre Synthesized from Empty Fruit Bunch Fibre - Ting Lee; Wan-Cheng Tan; Akihiko Matsumoto; Fei-Yee Yeoh (Adsorption Science & Technology)
In this article, the methane adsorption behaviour of activated carbon fibre (ACF), a nanoporous material, was examined for adsorbed natural gas (ANG) applications. The ACF was produced from palm fibre-based materials through carbonization, followed by CO 2 activation. The carbonization of empty fruit bunch (EFB) fibres was conducted at temperatures of 85–250 °C in an oxidative atmosphere. The produced ACF showed well-developed pore structure with high micropore volume and excellent pore-size distribution. The ACF, predominantly with microporous pores, fulfils the requirements as an excellent adsorbent for methane adsorption. The optimal carbonization conditions for improving methane adsorption capacity were achieved using concentrated H 2 SO 4 at 250 °C, followed by activation at 900 °C. Only physisorption occurred during the adsorption of methane on ACF. The EFB fibre-derived ACF has high potential for use in NG adsorption and storage applications via ANG technology.